Pharmacokinetics and renal safety of tenofovir alafenamide with boosted protease inhibitors and ledipasvir/sofosbuvir. (7th August 2020) - Brooks, Kristina M; Castillo-Mancilla, Jose R; Morrow, Mary; MaWhinney, Samantha; Blum, Joshua; Wyles, David L; Rowan, Sarah E; Ibrahim, Mustafa E; Zheng, Jia-Hua; Johnson, Bethany; Gomez, Joe; Choi, Ye Ji; et al.
Abstract: Background: Ledipasvir/sofosbuvir increases tenofovir plasma exposures by up to 98% with tenofovir disoproxil fumarate (TDF), and exposures are highest with boosted PIs. There are currently no data on the combined use of the newer tenofovir prodrug, tenofovir alafenamide (TAF), boosted PIs and ledipasvir/sofosbuvir. Objectives: To compare the plasma and intracellular pharmacokinetics and renal safety of TAF with ledipasvir/sofosbuvir when co-administered with boosted PIs. Methods: Persons with HIV between 18 and 70 years and on a boosted PI with TDF were eligible. The study was comprised of four phases: (1) TDF 300 mg with boosted PI; (2) TAF 25 mg with boosted PI; (3) TAF 25 mg with boosted PI and ledipasvir/sofosbuvir; and (4) TAF 25 mg with boosted PI. Pharmacokinetic sampling, urine biomarker collection [urine protein (UPCR), retinol binding protein (RBP) and β2 microglobulin (β2M) normalized to creatinine] and safety assessments occurred at the end of each phase. Plasma, PBMCs and dried blood spots were collected at each visit. Results: Ten participants were enrolled. Plasma tenofovir exposures were 76% lower and tenofovir-diphosphate (TFV-DP) concentrations in PBMCs increased 9.9-fold following the switch to TAF. Neither of these measures significantly increased with ledipasvir/sofosbuvir co-administration, nor did TAF plasma concentrations. No significant changes in estimated glomerular filtration rate or UPCR occurred, but RBP:creatinine and β2M:creatinine improved following the switch to TAF. Conclusions: Ledipasvir/sofosbuvir did not significantly increase plasma tenofovir or intracellular TFV-DP in PBMCs with TAF. These findings provide reassurance that the combination of TAF, boosted PIs and ledipasvir/sofosbuvir is safe in HIV/HCV-coinfected populations.